1983
DOI: 10.1007/bf01948131
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric chylous (lymph-containing) cyst

Abstract: Mesenteric cysts are uncommon entities and chyle (lymph)-containing cysts are the rarest of this group. A case report of a chylous cyst with CT demonstrating unique fat and soft tissue fluid-fluid levels is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…Considering the sonographic appearance, these findings are suggestive of the possibility that the specific gravity of the upper liquid component is less than that of water. CT findings of this condition were first reported by Rifkin et al [7] and van Mil et al [8]. As they described, the upper portion showed fat density and the lower showed water density by CT.…”
Section: Case Reportmentioning
confidence: 68%
“…Considering the sonographic appearance, these findings are suggestive of the possibility that the specific gravity of the upper liquid component is less than that of water. CT findings of this condition were first reported by Rifkin et al [7] and van Mil et al [8]. As they described, the upper portion showed fat density and the lower showed water density by CT.…”
Section: Case Reportmentioning
confidence: 68%
“…7 The sonographic appearance of these tumors has been reported to range from a welldefined, unilocular, anechoic cyst to multicystic masses, often with scattered internal echoes suggestive of infection. [8][9][10][11] Rifkin et al 12 suggested that fluid-containing masses with CT numbers consistent with fat and fluid layering on a decubitus view should suggest the diagnosis of a chylous mesenteric cyst. However, in the case reported by Pomper et al 13 the lesion appeared homogeneous and exhibited no fat-fluid layering on CT, which is in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenteric and omental cysts do not have specific signs or symptoms to allow their clinical diagnosis [3]. Since two initial reports of these sonographic appearance in 1975 [4,5], however, such lesions have been detected with an increasing frequency [6][7][8][9][10][11]. This article presents our experience with 15 additional cases evaluated at our institution during the past 12 years.…”
mentioning
confidence: 98%